STUDENTS’ PERCEPTION OF THE EDUCATIONAL ENVIRONMENT IN AN UNDERGRADUATE PAKISTANI MEDICAL COLLEGE: Students Preception of the Educational Environment - ., Brig Irfan Shukr; ., Abeera Choudry (Pakistan Armed Forces Medical Journal, 2013)
Objective: To evaluate the students’ perception of their educational environment.Study Design: Descriptive study.Place and Duration of Study: Army Medical College, in October 2011.Material and Method: Sixty undergraduate final year students of the Army Medical College were included in the study. Dundee Ready Education Environment Measure (DREEM) was used to measure the educational climate of the college. The questionnaire of each student was analyzed and used to measure their perception of learning, perception of teachers, academic self-perception, perception of atmosphere, and their social self-perception. The scores were analyzed to evaluate educational climate using SPSS version 17.Results: Eighty percent of students had the opinion that educational environment at Army Medical College Rawalpindi is more positive, than negative. The majority of students had a more positive perception of learning 42 (70%), and thought that the teaching was moving in the right direction 36 (60%). 49 (82%) students' perception of atmosphere was positive, and 45 (75%) students socially perceived the college not too bad.Conclusion: The study highlights good educational environment at Army Medical College, but finds some need, for change in the curriculum towards betterment.